Quantitative determination of sulforaphane from broccoli extract tablets and its role in the protection of acute liver injury induced by ethanol - LI Baolong; TIAN Sicong; TAN Jie; LI Bing; CHEN Jingyu; SHAN Yujuan (浙江大学学报. 农业与生命科学版)
Sulforaphane (SFN) is an isothiocyanate (ITC) which exists as a precursor of glucosinolate (GS) in various cruciferous vegetables especially in broccoli. Sulforaphane has been regarded as a potential of anti-cancer agent derived from diet, mostly because of its powerful induction of phase Ⅱ enzymes, and it is also acted as an antagonist of injury factors including lipopolysaccharide (LPS) and homocysteine (HCY). The present study aims to explore whether broccoli extract, rich in sulforaphane, can protect the acute liver injury induced by ethanol in mice or not.The quantity of sulforaphane in broccoli extract was detected by high performance liquid chromatography (HPLC). Hematoxylin-eosin (HE) staining was used to determine the pathological changes in C57BL/6 mice model with the acute liver injury induced by ethanol. The activities of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and alkaline phosphatase (ALP) in serum of mice were measured using semi-automatic biochemical analyzer.The results showed that the quantity of sulforaphane in the broccoli extract was 1.26 mg/tablet. Liver masses in all sulforaphane treatment groups were obviously reduced which were presented as the sharply decreased ratio of liver mass/body mass. The seriously pathological evidence was observed in ethanol treatment group, while less changes were seen in the sulforaphane treatment groups. Sulforaphane could dramatically inhibit the activities of ALT, AST and ALP in serum of mice induced by ethanol, with more obvious suppression in the moderate (40 mg/kg) and high-dose (80 mg/kg) groups, respectively.The result above indicates that the sulforaphane from broccoli extract tablets is able to protect the liver injury induced by ethanol.